Reconstructive Research – Beyond the Subjectivity and Objectivity of Interpretation. Based on an Example of Analysis of Difficult Situations in Professional Work in the Experience of Pedagogy Graduates - Urbaniak-Zając, Danuta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2017)
This article is of methodological form, i.e. the descriptions of difficult situations encountered by pedagogy graduates in their professional work and reported by them to the researcher in semi-structured interviews, are treated as illustrative empirical data submitted to analysis (the manner of analysis is more important than its subject). The analysis is conducted according to the guidelines and principles of objective hermeneutics. It consists in the reconstruction of intersubjectively understood (in this way objective) structures of meaning and sense, what allows to reconstruct more visibly the pattern of actions of a responding person. In the article the reconstruction of fragments of two pedagogy graduates’ statements is presented. It is preceded by a consideration of subjectivity – objectivity issue in empirical research as the features of data and the conduct of the researcher. Unlike in classical frameworks where these features are usually presented in opposition to each other, in the method of objective hermeneutics the objectivity (understood as intersubjectivity) is a condition for subjectivity, whereas subjectivity (individuality) is a condition for the change of existing structures.